Elliott's Wave theory in the field of econophysics and its application to the PSI20 in the context of crisis - Ribeiro, Sandra (2020)
In the last decades and in the scope of the economic sciences, new interdisciplinary forms have been developed, of which Econophysics stands out. It uses theoretical bases of physics and of statistical physics for the explanation of economic phenomena, particularly financial phenomena. This work shows, through statistical physics, possible forms of chart analysis of a stock exchange index, through the practical application of Elliott’s Wave Theory to the movement of the Portuguese stock index, the PSI20. With the empirical application made to the PSI20, we emphasize the degree of reliability that the Elliott method has demonstrated when applied to large indexes, generating projection scenariosbased on patterns of repetitive cyclic behaviour. It is possible, and for several moments, to identify the Elliott wave pattern, namely in the crisis period.